Diagnostic accuracy of a liquid chromatography-tandem mass spectrometry assay in small hair samples for rifampin-resistant tuberculosis drug concentrations in a routine care setting - Metcalfe, John; Bacchetti, Peter; Esmail, Ali; Reckers, Andrew; Aguilar, David; Wen, Anita; Huo, Shu; Muyindike, Winnie R.; Hahn, Judith A.; Dheda, Keertan; Gandhi, Monica; Gerona, Roy (BMC infectious diseases, 2021)
Background: Treatment monitoring of drug-resistant tuberculosis (DR-TB) in resource-limited settings is challenging. We developed a multi-analyte assay for eleven anti-TB drugs in small hair samples as an objective metric of drug exposure. Methods: Small hair samples were collected from participants at various timepoints during directly observed RR-TB treatment at an inpatient tertiary referral facility in South Africa (DR-TB cohort). We assessed qualitative determination (i.e., detection above limit of detection) of bedaquiline, linezolid, clofazimine, pretomanid, levofloxacin, moxifloxacin, pyrazinamide, isoniazid, ethambutol, ethionamide, and prothionamide in an LC-MS/MS index panel assay against a reference standard of inpatient treatment records. Because treatment regimens prior to hospitalization was not available, we also analyzed specificity (for all drugs except isoniazid) using an external cohort of HIV-positive patients treated for latent TB infection with daily isoniazid (HIV/LTBI cohort) in Uganda. Results: Among the 57 DR-TB patients (58% with pre-XDR/XDR-TB; 70% HIV-positive) contributing analyzable hair samples, the sensitivity of the investigational assay was 94% or higher for all drugs except ethionamide (58.5, 95% confidence interval [CI], 40.7–99.9). Assay specificity was low across all tested analytes within the DR-TB cohort; conversely, assay specificity was 100% for all drugs in the HIV/LTBI cohort. Conclusions: Hair drug concentrations reflect long-term exposure, and multiple successive regimens commonly employed in DR-TB treatment may result in apparent false-positive qualitative and falsely elevated quantitative hair drug levels when prior treatment histories within the hair growth window are not known
Keywords: LC-MS/MS; Hair; Multidrug-resistant tuberculosis